Bank competition and firms' dependence: evidence from firms' role. Issue 10 (25th February 2021) - Wang, Chih-Wei; Lee, Chien-Chiang; Yin, Chi; Choo, Min-Rui
ABSTRACT: This research provides empirical evidence on bank-firm relationships from firms' role in discussing their dependence on banks from the perspectives of bank competition. Using a rich dataset of loans, we find that firms reduce their dependence on banks when banks operate in a more competitive environment. These effects are more pronounced when firms are financially distressed and constrained. Moreover, firms with active family control exhibit less dependence on lenders in a competitive environment. Our evidence provides specific strategies and self-consideration of borrowers and lenders.